Religion and Spirituality: A Phenomenological Approach - Irawan, Dedi; Muhammad Akhmad, Firdausi (Green Publisher Indonesia, 2025)
This paper attempts to map phenomenology as an approach to understanding religion and spirituality. Phenomenology in a general sense is knowledge as it appears in consciousness and is used as one approach to understanding religion. This paper lays out the paradigm of the transformation of pure phenomenology to the phenomenology of religion, with the aim of better understanding the religious phenomena that produce deep meaning. In addition, this paper describes the definition, brief history, and problems in phenomenology. This research method is a literature study with a descriptive-analytical approach. The result of this research is that the phenomenological approach is still relevant and effective to read the phenomena of religion and spirituality in modern society, especially to explore the meaning of individual human experiences.